VprBP binds full-length RAG1 and is required for B-cell development and V(D)J recombination fidelity - Kassmeier, Michele D (Nature Publishing Group, 2012)
The N-terminus of full-length RAG1, though dispensable for RAG1/2 cleavage activity, is required for efficient V(D)J recombination. This region supports RING E3 ubiquitin ligase activity in vitro, but whether full-length RAG1 functions as a single subunit or a multi-subunit E3 ligase in vivo is unclear. We show the multi-subunit cullin RING E3 ligase complex VprBP/DDB1/Cul4A/Roc1 associates with full-length RAG1 through VprBP. This complex is assembled into RAG protein–DNA complexes, and supports in-vitro ubiquitylation activity that is insensitive to RAG1 RING domain mutations. Conditional B lineage-specific VprBP disruption arrests B-cell development at the pro-B-to-pre-B cell transition, but this block is bypassed by expressing rearranged immunoglobulin transgenes. Mice with a conditional VprBP disruption show modest reduction of D–J(H) rearrangement, whereas V(H)–DJ(H) and V(κ)–J(κ) rearrangements are severely impaired. D–J(H) coding joints from VprBP-insufficent mice show longer junctional nucleotide insertions and a higher mutation frequency in D and J segments than normal. These data suggest full-length RAG1 recruits a cullin RING E3 ligase complex to ubiquitylate an unknown protein(s) to limit error-prone repair during V(D)J recombination.